2019
DOI: 10.1177/2057158519866612
|View full text |Cite
|
Sign up to set email alerts
|

Information retrieval as a part of evidence-based practice: Retrieval skills, behavior and needs among nurses at a large university hospital

Abstract: Nurses are required to apply research-based knowledge in order to perform evidence-based practice. A survey was conducted to identify nurses’ information-retrieval skills, behavior and needs and replies were received from 1301 nurses. The most used electronic resources for retrieval of healthcare information were the local intra-net and Google, while bibliographic databases were used to a lesser extent. Half of the respondents indicated that they were accustomed to search databases and an equal number indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although we previously conducted research on PoCTs, including nurses' voices was essential. Consistent with previous studies, more nurses need to be trained how to use them effectively for best practice [ 6 , 13 14 ]. This provides opportunities for librarians to educate nurses on best practices for searching.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Although we previously conducted research on PoCTs, including nurses' voices was essential. Consistent with previous studies, more nurses need to be trained how to use them effectively for best practice [ 6 , 13 14 ]. This provides opportunities for librarians to educate nurses on best practices for searching.…”
Section: Discussionmentioning
confidence: 63%
“…While previous research has investigated the effectiveness of nurses' information seeking [13][14][15][16], these survey responses may indicate the need to further explore nurses' information needs and information-seeking behaviors more broadly. No PoCT received high ratings, and negative comments about searching were reported across the PoCTs.…”
Section: Discussionmentioning
confidence: 99%
“…These barriers are also mentioned in current and previous discussed studies. Lee et al (2019) explored Danish nurses’ information retrieval and found the local intranet and Google as the primary electronic resources. We found the way nurses integrated EBP in a busy workday, was through available clinical guidelines found on the local intranet and by asking the nurses in charge of development.…”
Section: Discussionmentioning
confidence: 99%
“…It also may uncover common patterns and variations in methods of seeking health information among NISs across diverse cultural and clinical placement contexts. In recent years, there has been a growing emphasis on promoting the use of EBHI and enhancing health literacy [15,30]. There is a significant correlation between nursing students' ISBs and their preference for EBHI.…”
Section: Introductionmentioning
confidence: 99%